The Role of Stakeholders in Marketing Communication at the Archaeological Museum to Increase Tourist Visits - Dhony Hardiyanto; Mahendra Wijaya; Ign. Agung Satyawan; Minto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The main problem faced is the decline in tourist visits over the past six years and the lack of marketing communication innovations that hinder potential visits. The method used is descriptive qualitative, with observation techniques, in-depth interviews, and documentation, and the selection of informants using purposive sampling, namely the Sragen Regency Youth, Sports, Museum and Cultural Heritage Office, Krikilan Village Government, Pokdarwis Purba Budaya, Tourists. The theory used includes the SOSTAC + 3Ms model from PR Smith. The results and discussion show that the marketing strategy implemented is still less than optimal because it is too focused on print media advertising, merchandise, and personal promotion through fam trips, and minimal use of digital media. The main stakeholders emphasise the role of education, while other stakeholders, such as Pokdarwis and Krikilan Village Government, are still less active in promotion. In conclusion, the marketing communication strategy of Sangiran Museum of Ancient Humans needs to be developed with the utilisation of more digital channels and more active involvement of secondary stakeholders